AtCRK5 Protein Kinase Exhibits a Regulatory Role in Hypocotyl Hook Development during Skotomorphogenesis - Baba, Abu Imran; Andrási, Norbert; Valkai, Ildikó; Gorcsa, Teréz; Koczka, Lilla; Darula, Zsuzsanna; Medzihradszky, Katalin F; Szabados, László; Fehér, Attila; Rigó, Gábor; Cséplő, Ágnes (International journal of molecular sciences, 2019)
Seedling establishment following germination requires the fine tuning of plant hormone levels including that of auxin. Directional movement of auxin has a central role in the associated processes, among others, in hypocotyl hook development. Regulated auxin transport is ensured by several transporters (PINs, AUX1, ABCB) and their tight cooperation. Here we describe the regulatory role of the Arabidopsis thaliana CRK5 protein kinase during hypocotyl hook formation/opening influencing auxin transport and the auxin-ethylene-GA hormonal crosstalk. It was found that the Atcrk5-1 mutant exhibits an impaired hypocotyl hook establishment phenotype resulting only in limited bending in the dark. The Atcrk5-1 mutant proved to be deficient in the maintenance of local auxin accumulation at the concave side of the hypocotyl hook as demonstrated by decreased fluorescence of the auxin sensor DR5::GFP. Abundance of the polar auxin transport (PAT) proteins PIN3, PIN7, and AUX1 were also decreased in the Atcrk5-1 hypocotyl hook. The AtCRK5 protein kinase was reported to regulate PIN2 protein activity by phosphorylation during the root gravitropic response. Here it is shown that AtCRK5 can also phosphorylate in vitro the hydrophilic loops of PIN3. We propose that AtCRK5 may regulate hypocotyl hook formation in Arabidopsis thaliana through the phosphorylation of polar auxin transport (PAT) proteins, the fine tuning of auxin transport, and consequently the coordination of auxin-ethylene-GA levels.
Keywords: Morphogenesis; Phenotype; Germination; Arabidopsis Proteins; biologické markery; Biomarkers; reportérové geny; morfogeneze; xantony; Protein Serine-Threonine Kinases; signální transdukce; hypokotyl; Signal Transduction; proteiny huseníčku; Hypocotyl; fosforylace; Plant Development; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; receptory buněčného povrchu; Xanthones; Receptors, Cell Surface; Arabidopsis; fenotyp; Genes, Reporter; vývoj rostlin; protein-serin-threoninkinasy; Phosphorylation; klíčení